Interest rate conundrums in the twenty-first century - Samuel G. Hanson; David O. Lucca; Jonathan H. Wright (Federal Reserve Bank of New York, 2017)
A large literature argues that long-term interest rates appear to react far more to high-frequency (for example, daily or monthly) movements in short-term interest rates than is predicted by the standard expectations hypothesis. We find that, since 2000, such high-frequency "excess sensitivity" remains evident in U.S. data and has, if anything, grown stronger. By contrast, the positive association between low-frequency changes (such as those seen at a six- or twelve-month horizon) in short- and long-term interest rates, which was quite strong before 2000, has weakened substantially in recent years. As a result, "conundrums" - defined as six- or twelve-month periods in which short rates and long rates move in opposite directions - have become far more common since 2000. We argue that the puzzling combination of high-frequency excess sensitivity and low-frequency decoupling between short- and long-term rates can be understood using a model in which (i) shocks to short-term interest rates lead to a rise in term premia on long-term bonds and (ii) arbitrage capital moves slowly over time. We discuss the implications of our findings for interest rate predictability, the transmission of monetary policy, and the validity of high-frequency event study approaches for assessing the impact of monetary policy.
Keywords: E43; E52; G12; 330; interest rates; conundrum; monetary policy transmission